2018
DOI: 10.1111/bjd.16935
|View full text |Cite
|
Sign up to set email alerts
|

Short contact with nickel causes allergic contact dermatitis: an experimental study

Abstract: This experimental study showed that relatively short repeated skin contact (3 × 10 min) with metallic nickel elicits allergic nickel dermatitis in irritated skin and at sites with previous dermatitis. The results support the restrictions in current nickel regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…Furthermore, the case shows that brief and repeated nickel skin contact at work can lead to nickel skin deposition and chronic hand eczema. The importance of this has recently been highlighted experimentally …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the case shows that brief and repeated nickel skin contact at work can lead to nickel skin deposition and chronic hand eczema. The importance of this has recently been highlighted experimentally …”
Section: Discussionmentioning
confidence: 99%
“…Although the current main causes of nickel allergy and dermatitis are presumed to be well‐known risk items such as earrings and jewellery, the widespread use of nickel may be of importance for the continuing high prevalence of nickel allergy . Recent reports have shown that various metallic items intended for short but repeated skin contact can lead to accumulation of nickel on the skin over time . These exposures may not be as obvious and may therefore not be studied to the same extent, which is why little is known about their clinical implications.…”
Section: Sources Of Nickel Exposurementioning
confidence: 99%
“…Nielsen et al showed a worsening of existing hand eczema in nickel‐allergic individuals after finger exposure for 10 minutes daily to 10 ppm and then 100 ppm nickel over a 2‐week period . In a recent study, it was shown that three 10‐minute exposures to metallic nickel discs led to elicitation of allergic nickel dermatitis in pre‐irritated skin in 10 of 16 nickel‐allergic individuals . Also, it has been shown that relatively short and repeated occupational skin contact with nickel can lead to hand eczema in nickel‐allergic individuals Nickel probably builds up on or in the skin after repeated contact at the same skin site.…”
Section: Thresholds For Nickel Allergymentioning
confidence: 99%
“…Nickel is toxic to humans. It frequently elicits contact allergy acting via skin exposure to materials releasing this metal . Unfortunately, many objects of daily use, such as tools, coins, jewelry, or cases of mobile phones and laptops release nickel in amounts high enough to trigger a reaction of the human immune system .…”
Section: Introductionmentioning
confidence: 99%